Simbol untuk Menunjang Sistem Informasi Desain Kemasan Makanan dan Minuman Plastik - Devi Kurniawati Homan (Humaniora, 2011)
The use of plastic as packaging food and beverages has increased along with the development of technological and cultural changes in society. But this change has not been followed by an adequate understanding of the various types of plastic and usefulness. Symbols and information system on packaging become important information for consumer and visual communication designer. Based on field research, literature research and desktop research, the author summarizes that the information in the form of significant symbols are important to be put on the design of plastic packaging for food or beverage. During this time, several foods and beverages in plastic packaging have included the plastic code. But generally consumers do not have enough knowledge about these codes. This is where the role of visual communication designers becomes an important. Symbols and information systems which prepared in well design will be more easily to understand. With easily understandable symbol and information systems, consumer certainly would be wiser to choose and avoid the negative impact during the bad use of food and beverage plastics packaging.